2014
DOI: 10.1016/j.celrep.2014.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Acts as a Key Signal Linking Glucose Metabolism to Incretin/cAMP Action to Amplify Insulin Secretion

Abstract: SummaryIncretins, hormones released by the gut after meal ingestion, are essential for maintaining systemic glucose homeostasis by stimulating insulin secretion. The effect of incretins on insulin secretion occurs only at elevated glucose concentrations and is mediated by cAMP signaling, but the mechanism linking glucose metabolism and cAMP action in insulin secretion is unknown. We show here, using a metabolomics-based approach, that cytosolic glutamate derived from the malate-aspartate shuttle upon glucose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 62 publications
9
150
1
Order By: Relevance
“…The EGCG inhibition was associated with reduced glutamate levels, substantiating the cataplerotic activity upon glucose stimulation in human islets. Glutamate is the GDH cataplerotic product required for amplifying glucose-stimulated insulin exocytosis (Gheni et al, 2014;Maechler and Wollheim, 1999). When reverse anaplerotic activity of GDH was imposed in both mouse and human islets by the combination of glutamine + BCH, EGCG decreased insulin release, confirming previous observations in rat islets.…”
Section: Discussionsupporting
confidence: 82%
“…The EGCG inhibition was associated with reduced glutamate levels, substantiating the cataplerotic activity upon glucose stimulation in human islets. Glutamate is the GDH cataplerotic product required for amplifying glucose-stimulated insulin exocytosis (Gheni et al, 2014;Maechler and Wollheim, 1999). When reverse anaplerotic activity of GDH was imposed in both mouse and human islets by the combination of glutamine + BCH, EGCG decreased insulin release, confirming previous observations in rat islets.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, independent research groups reported glutamate uptake by insulin vesicles, rendering these granules exocytosis competent [2]. Interestingly, a recent study demonstrated that the action of glutamate is stimulated by cAMP, a second messenger induced by GLP-1, thereby unifying two signals controlling insulin secretion in pancreatic b-cells [8].…”
Section: 2mentioning
confidence: 99%
“…Finally, the presence of depolarising agents and the allosteric K ATP channel activator diazoxide can further enhance insulin secretion in response to glucose [16]. As a result, additional factors that drive metabolism-dependent secretion, such as mitochondrial metabolites (NADPH, GTP, phosphoenol pyruvate [PEP], α-ketoglutarate [α-KG]), and other secondary glucose-derived metabolites such as glutamate [17,18] must exist.…”
Section: Introductionmentioning
confidence: 99%